How can Azerbaijan meet its Paris Agreement commitments: assessing the effectiveness of climate change-related energy policy options using LEAP modeling - Troy B. Felver (Heliyon, 2020)
Azerbaijan has committed to cut GHG emissions by 35% by 2030 under the Paris Agreement. By applying LEAP, a well-regarded forecasting model based on inventories defined under the IPCC (Intergovernmental Panel on Climate Change), GHG emissions projections are modeled in three scenarios: a without measures (WOM) scenario or business-as-usual, which assumes no change to current behavior, a with existing measures (WEM) scenario, which takes into account currently planned measures in Azerbaijan, and an EU policy scenario, which mirrors the existing mitigation measures of the European Union. The WOM scenario of total GHG emissions from the energy sector indicates that from 2010 to 2030, total emissions will increase by 67% in Azerbaijan. In the WEM scenario, forecasted GHG emissions are only 29.7% lower than the base year and still above the nation's Paris Agreement commitment. In the EU policy scenario, projected GHG emissions are 37.2% lower than the base year. Therefore, current mitigation measures are insufficient for Azerbaijan to meet its commitments to the Paris Agreement, and stronger measures than currently planned are necessary. Because of its status as a developing nation with limited resources, Azerbaijan must have funding from developed nations promised under the Paris Agreement to transition towards a less carbon-heavy economy.